Effect of Neosaxitoxin on Epidural Anesthesia in Cats: a Promising Alternative to Conventional Anesthetics - Varela Xaviera; del Campo Miguel; Piron Robin; Sepulveda Joaquín; Bustamante Tamara; Hinzpeter Jaime; Lagos Néstor (International Physiology Journal, 2019)
Neosaxitoxin (NeoSTX) is a specific high-affinity inhibitor of voltage-dependent sodium channels, which has shown excellent results as a local anesthetic in various pathologies and post-operative protocols, since it effect is long-lasting and have virtually no side effects.The aim of this study was to analyze the effect of NeoSTX as an epidural anesthetic in female cats, undergoing ovariohysterectomy, compared to Lidocaine in a randomized and double-blind study. Two groups of 11 female cats were randomly in the NeoSTX group and the lidocaine group. They were administered, respectively, a single dose of NeoSTX (0.5 μg / kg) or lidocaine (4 mg / kg, 2%) by epidural via. Using the UNESP-Botucatu pain assessment scale, which considers multiple behavioral and physiological factors, the epidural anesthetic effect of NeoSTX and lidocaine was evaluated, up to 240 min after the ovariohysterectomy procedure. NeoSTX no altered the peripheral blood pressure during the cut of uterine cervix, and generated lower values on the pain scale as compared to the lidocaine treatment. None of the cats anesthetized with NeoSTX required an extra dose of pain-relieving drugs (2 mg / kg of tramadol) during the first 150 min after surgery, whereas nine cats from the lidocaine group did need an extra dose of analgesic. NeoSTX is a powerful pain blocker, with a long-lasting anesthetic effect when administered by an epidural procedure. Therefore, NeoSTX emerges as a promising alternative to conventional anesthetics for the treatment of postoperative pain.
Keywords: Paralytic Shellfish Toxins